Are we still misdiagnosing clubfoot? A study of non-clubfoot cases labeled or referred as clubfoot from primary care centers in Uttarakhand - Dharmshaktu, Ganesh Singh; Dar, Alamgir Jhan; Bhandari, Shailendra Singh (Indian Journal of Child Health, 2018)
Background: Clubfoot is a congenital disorder identifiable with the clinical assessment itself, provided the knowledge of key features is sound. Several disorders affecting the foot and lower limb that present with crooked or bent anatomy may be confused with it. Knowledge of common disorders that mimic clubfoot in a particular region is thus important to adequately distinguish, manage or refer the case to specialist opinion. Objectives: The current study attempts to provide an overview and documentation of the conditions referred and labeled as clubfoot from primary care facilities, the knowledge of which is important so that appropriate treatment is given to each. The findings will reflect lacunae in the knowledge and perception of primary healthcare workers regarding the deformity. Materials and Methods: A retrospective assessment of all cases referred to our dedicated clubfoot clinic with a diagnosis of clubfoot by peripheral health-care facility was done from September 2016 to October 2017. Relevant demographic details including that of parents, type of deformity, nature, laterality, and treatment received were noted for each case. Conditions requiring non-operative treatment and those requiring further evaluation were noted separately with a detailed description. Results: Out of total 97 cases labeled as clubfoot, 32 (33.68%) cases with 64 feet were part of the study after excluding true clubfoot cases. The common condition noted was calcaneovalgus, postural clubfoot, equinus deformity secondary to cerebral palsy, metatarsus adductus, in-toeing, and posteromedial bowing of tibia. Conclusion: The knowledge of common foot disorders in primary care settings should be strengthened by refresher practical training so that these disorders are diagnosed and managed there an appropriate referral is made thus leading to decrease the burden on higher centers.